Aceptación de vinos portugueses de las marcas Mateo e Sequeira Vinos S.A. y Quinta Da Mata Fidalga, por parte de los distribuidores de vinos de la GAM durante el primer semestre de 2018 - Alvarado-Campos, Priscila; Herrera-Morice, Adriana (Instituto Tecnológico de Costa Rica, 2018)
The purpose of this research is to contribute to the feasibility studies of a new business project that is seen as the creation of a company that imports Portuguese wines. The aproach is to simplify the business and sell directly to the wine distributors in Costa Rica, since they have the experience, truck fleet and developed routes. The objective of this study is to identify the acceptance of Portuguese wines of the Mateo and Sequeira Vinos S.A. brands, and Quinta Da Mata Fidalga, by the wine distributors in the GAM during the first half of 2018. The question that this research aims to solve is: ¿There is acceptance of Portuguese wines of the brands Mateo e Sequeira Vinos S.A. and Quinta Da Mata Fidalga, among the wine distributors of the GAM during the first half of 2018? To carry out this study, it was determined to work with the wine distributors located within the GAM of Costa Rica as a market niche, which represent a size of 34 distributors. This study was worked through a census. The position of Portuguese wines, at the level of distributors of the GAM is low. When evaluating the acceptance of the brands Mateo and Sequeira Vinos S.A. and Quinta Da Mata Fidalga, among the distributors of GAM wines, a 42% acceptance is obtained. Distributors who indicate a negative, suggest an opportunity because the reasons presented are lack of knowledge and local suppliers. For distributors, the main attributes they take into account to introduce into their portfolio are price and quality. For the launch of the project it is recommended to carry out a strong communication strategy, participate in fairs and exhibitions, introduce the product through presentations and tastings.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2018.
Keywords: Vinos; Distribución; GAM; Viabilidad; Investigación